Performance of improved varieties and technological interventions at farmers’ fields for cumin cultivation - A S Godara, H Cheriyan, G Lal, R S Mehta, P Chand, (Journal of Spices and Aromatic Crops, 2015)
Front line demonstrations on cumin consisting of two improved varieties (GC-4 and RZ-209) with scientific interventions viz., seed treatment (Bavistin @2.5 g kg-1 seed and Trichoderma viride @4 g kg-1 seed), and pre-emergence application of oxadiragil (Raft) @75 g a.i. ha-1 for effective weed management and application of recommended doses of nutrients (40:40:0 kg ha-1 NPK) for balanced nutrition and appropriate plant protection schedule [(Two sprays of malathion (0.2%), two sprays of Dithan M-45 (0.2%) and one spray of karathan (0.1%) for the control of aphids, blight and powdery mildew, respectively)] were carried out at farmers’ fields in two villages (Kajipura and Bhadal) of Jaipur and one village (Karad) of Sikar district of Rajasthan during Rabi season of 2011–12 and 2012–13. Study revealed that overall yield was increased by 21.09% over farmers’ practice due to the technological interventions with average yield of 536.50 kg ha-1. Overall extension gap of 112.50 kg ha-1 and technical gap of 463.50 kg ha-1 were recorded in the study with 46.35% technology index. Maximum additional return (Rs. 15,875 ha-1) with highest effective gain (Rs. 10,775 ha-1) and incremental B: C ratio (3.11) were obtained in the year 2011–12. However, the overall average additional return was Rs. 14601 ha-1 with effective gain of Rs. 9,401 ha-1 and incremental B: C ratio of 2.81.